EDITORIAL: PILAR PERAWATAN MANDIRI DIABETES MELLITUS: Editorial: Pillars of Diabetes Mellitus Self-Care - Sugiharto (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2021)
Diabetes Meliitus merupakan penyakit kronik. Perawatan mandiri penderita DM bertujuan untuk mengelola penyakit terhadap dampak fisiologis, emosi dan hubungan interpersonal. Pada tahun 2014, American Association of Diabetes Educators (AADE) merumuskan ada tujuh pilar perawatan mandiri DM, antara lain: Pola makan yang sehat, Aktif secara fisik/aktif bergerak, minum obat, pemantauan, pemecahan masalah, mekanisme koping yang sehat, dan mengurangi resiko. Diabetes Mellitus is a chronic disease. Self-care for DM sufferers aims to manage the disease on its physiological, emotional and interpersonal relationships. In 2014, the American Association of Diabetes Educators (AADE) formulated seven pillars of DM self-care, including: a healthy diet, being physically active/actively moving, taking medication, monitoring, problem solving, healthy coping mechanisms, and reducing stress. risk.